Cash Flow, Board Independence, Financial Distress in State-Owned Enterprises (SOE) Companies in Indonesia - Hans Hananto Andreas (KRISNA: Kumpulan Riset Akuntansi, 2024)
The purpose of this study was to investigate the impact of cash flow and board independence on financial distress in Indonesian state-owned corporations (BUMN). The sample in this study used 60 data from 20 state-owned companies listed on the Indonesia Stock Exchange in 2019-2021. The results of the cash flow research have no effect on financial distress, and board independence has no effect on financial distress. However, because BUMN is a government-owned company that is very closely connected to politics, using additional analysis in the form of political connections, it was found that political connections had an effect on financial distress. These findings show that the political connections that state-owned companies have can have a positive impact on the company, for example, in getting money loans from banks, tax discounts given by the DJP, preferential treatment in accepting contracts or projects from the government, or having ease in licensing. We suspect that this can reduce the chances of state-owned companies experiencing financial distress if they have political connections.